Strategi dan Metode Pembelajaran Tahsinul Quran di Madrasah Aliyah Annur Prima Medan - Pratama Muhammad Panjaitan; Lasmidah Lasmidah; Hasrian Rudi Setiawan (STIKes Ibnu Sina Ajibarang, 2023)
Learning tahsinul quran has become very important in the current era, especially in public and private schools that teach Al-Quran learning, and in the city of Medan there are several schools that implement this learning. This research aims to find out the learning strategies and methods used at Madrasah Aliyah Annur Prima Medan. The method used in this research is a qualitative method with data collection techniques, observation and documentation. The results of this research show that tahsinul Koran learning at Madrasah Aliyah Annur Prima uses strategies and methods that are varied and not monotonous, and from the results of this research it can be concluded that Madrasah Aliyah Annur Prima Medan really maximizes the human resources and learning resources available at the school.